1913 N.Y. Laws 1627-30, § 1 - (:unkn) unknown (My University, 1913)
Vol. III, ch. 608, § 1, Carrying and Use of Dangerous Weapons Carrying Weapons, Dangerous or Unusual Weapons, § 1; Prohibited the carrying or possession of any weapon of the kind commonly known as a blackjack, slungshot, billy, sandclub, sandbag, metal knuckles, bludgeon, bomb, or bombshell, and the carrying or possession of any dagger, dirk, dangerous knife, razor, stiletto, or other "dangerous or deadly instruments or weapon."
Keywords: POSSESSION - NON-GUN ARMS